2008
DOI: 10.1149/1.2822885
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N[sub 2]O Plasma Treatment on the Performance of ZnO TFTs

Abstract: Postfabrication rapid thermal annealing ͑RTA͒ and subsequent nitrous oxide ͑N 2 O͒ plasma treatment improved the performance of zinc oxide ͑ZnO͒ thin-film transistors ͑TFTs͒ in terms of off current and on/off current ratio by almost 2 orders of magnitude. The off current of 2 ϫ 10 −8 A and on/off current ratio of 3 ϫ 10 3 obtained after RTA were improved to 10 −10 A and 10 5 , respectively, by the subsequent N 2 O plasma treatment. X-ray photoelectron spectroscopy analysis of the TFT samples showed that the RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 23 publications
(34 reference statements)
2
31
0
Order By: Relevance
“…In order to differentiate the XPS measurements, the typical O 1s peak was divided into three peaks through Gaussian fitting, as shown in Figure 5. The deconvoluted results of the O 1s peaks exhibited a peak at around 529.6 eV (O I ), which is ascribed to the O 2 − ions among metal oxides; a second peak, around 531.1 eV (O II ), is usually attributed to the oxygen vacancies in the film; the third peak, located at about 531.7 eV, is related to weakly bound oxygen species on the film surface, such as CO 3 , OH − , or adsorbed O 2 [16]. The relative ratio of O II /O total are 36.4%, 35.2%, 33.8%, and 28.8% for pO 2 = 0%, 5%, 10%, and 20%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In order to differentiate the XPS measurements, the typical O 1s peak was divided into three peaks through Gaussian fitting, as shown in Figure 5. The deconvoluted results of the O 1s peaks exhibited a peak at around 529.6 eV (O I ), which is ascribed to the O 2 − ions among metal oxides; a second peak, around 531.1 eV (O II ), is usually attributed to the oxygen vacancies in the film; the third peak, located at about 531.7 eV, is related to weakly bound oxygen species on the film surface, such as CO 3 , OH − , or adsorbed O 2 [16]. The relative ratio of O II /O total are 36.4%, 35.2%, 33.8%, and 28.8% for pO 2 = 0%, 5%, 10%, and 20%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The Ti/ Al/Ti ͑50/200/50 nm͒ source/drain electrodes were formed by sputtering and then patterned into the dimension of channel width/length ͑W / L͒ =5-30 m / 7 m. A 30 nm thick a-IGZO film was deposited by dc magnetron sputtering system at room temperature, using a target of In: Ga: Zn =1:1:1 in atomic ratio, a plasma discharge power of 300 W, and in an ambiance of gas mixture ratio of O 2 / Ar= 6.7% with a working pressure of 5 mTorr. 15 The excellent SS of 0.28 V/dec reveals only a few interface states were remained. Finally, all of devices were capped with a 200 nm SiO x layer by PECVD at 170°C, and sequentially annealed in an oven at 330°C for 2 h. The electrical properties of a-IGZO TFTs with L =7 m and W = 30 m were analyzed by using Agilent 4156-C system in dark, and characterized at 30°C in vacuum with a pressure of 10 −2 Torr to avoid the interference from environment.…”
Section: Influence Of Positive Bias Stress On N 2 O Plasma Improved Imentioning
confidence: 98%
“…Its unique electrical and optical properties have made it popular in piezoelectric transducers, surface acoustic wave (SAW) devices, laser diodes, photoconductive UV detectors, gas sensors, etc. Several reports [3][4][5] have indicated that ZnO TFTs exhibited a high off-current (I off ) and a low on-to-off current ratio because a transistor with an active channel layer made from undoped ZnO film has a high carrier density that causes the channel to conduct when an applied gate voltage is absent. It has been demonstrated that the electrical characteristics of ZnO films can be controlled by doping with ternary elements 6,7) or by heat treatment processes.…”
Section: Introductionmentioning
confidence: 99%